Incidence of symptomatic and asymptomatic plasmodium falciparum infection following curative therapy in adult residents of northern Ghana. - Owusu-Agyei, S.; Koram, K.A.; Baird, J.K.; Utz, G.C.; Binka, F.N.; Nkrumah, F.K.; Fryauff, D.J.; Hoffman, S.L. (American Journal of Tropical Medicine and Hygiene, 2001)
Adult residents of holoendemic malaria regions in Africa have a naturally acquired immunity (NAI) to malaria that renders them more resistant to new infections, limits parasitemia, and reduces the frequency and severity of illness. Given such attributes, it is not clear how one might evaluate drug or vaccine efficacy in adults without serious confounding. To determine symptomatic and asymptomatic malaria attack rates in adults of northern Ghana, 197 men and women underwent curative therapy for any pre-existing malaria infections at the start of the high transmission (wet) season. They were monitored for first parasitemia and first clinical episode of infection by Plasmodium falciparum over a 20-week period (May-October 1996). The cumulative incidence of primary infection by P. falciparum was 0.98 and incidence density of infection was calculated to be 7.0 cases/person-year. Symptoms were reported by 19.5% of the individuals at the time of first recurrent parasitemia. Incidence of infection, parasite density, and the frequency of symptoms were comparable in males and females. The results suggest that NAI did not provide these adults with significant defense against rapid re-infection and suggest that this population-infection design could serve to demonstrate the efficacy of a drug or vaccine in preventing parasitemia.